Laparoscopic Pyelolithotomy: Comparison of Surgical Outcomes in Relation to Stone Distribution Within the Kidney - Lee, Jeong Woo (Mary Ann Liebert, Inc., 2013)
PURPOSE: To evaluate surgical outcomes of laparoscopic pyelolithotomy (LP) in relation to stone distribution within the kidney. METHODS: Between August 2008 and February 2012, 77 patients underwent LP as first-line treatment for renal stone(s). Cases were classified into four groups, depending on stone location: Group I (located in only renal pelvis), Group II (located only in renal calyx), Group III (located in renal pelvis and in one calyx), and Group IV (located in renal pelvis and in multiple calyces). Patient and stone characteristics, surgical outcomes, and complications were evaluated. RESULTS: Sixty-seven (81.8%) cases were stone-free after LP for large renal stones. Stone-free rates in a single session significantly decreased with greater stone dispersion (p<0.001). Mean hospital stay in group IV was significantly longer than in other groups (p=0.038). However, there were no significant differences in mean operation times (p=0.214), mean change in serum hemoglobin (p=0.709), postoperative analgesics usages (p=0.153), and number of analgesics used on an as-needed basis (p=0.079). There were no complications of grade IIIb or of greater severity. One patient in group II received blood transfusion, and 1 in group III required percutaneous drainage due to perirenal urine collection. CONCLUSIONS: LP is an effective and safe modality for managing renal stones diseases. Distribution of stone burden, and total stone burden, is an important predictor of surgical outcome of LP in renal stone diseases.